Evaluating the Implementation of Accounting Practices in Village-Owned Enterprises (BUMDes) in Indonesia: A Case Study of Awunio Village Under SAK EMKM Financial Reporting - Maimuna, Yuni; Adriani, Ulvi; Limbong, Diamond; Wahud, Fitria; Musa, Marsuddin (University Merdeka Malang, 2025)
This study evaluates the implementation of accounting practices in Village-Owned Enterprises (BUMDes) in Awunio Village, Kolono District, Indonesia, focusing on compliance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Using a qualitative descriptive approach, data were collected through interviews with BUMDes management and documentation analysis. Findings reveal that BUMDes in Awunio Village has not fully adhered to SAK EMKM requirements, reporting only chair rental income and expenses without presenting a balance sheet, profit/loss statement, or financial notes. This deficiency stems from a lack of training on standardized financial reporting, limiting transparency and accountability. The study highlights the need for capacity-building initiatives to enhance financial literacy among BUMDes managers and align reporting practices with regulatory frameworks. Results underscore the importance of robust financial management in sustaining rural enterprises and achieving community economic development. The research contributes to the discourse on micro-enterprise governance in Indonesia and offers actionable insights for policymakers and practitioners seeking to improve rural financial ecosystems.